2008
DOI: 10.1111/j.1600-051x.2008.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of periodontal treatment on IL‐1β, IL‐1ra, and IL‐10 levels in gingival crevicular fluid in patients with aggressive periodontitis

Abstract: The periodontal treatment improves the clinical parameters in G-AgP, and this improvement is evident in deep pocket sites for pocket depth and CAL values. These results confirm that IL-1beta is effective for evaluating the periodontal inflammation and can thus be used as a laboratory tool for assessing the activity of periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 33 publications
3
64
1
2
Order By: Relevance
“…5,17 The role of IL-1RA as an important inhibitor of bone remodeling is well documented in the literature, 3,18 and some studies show a positive correlation between decreased levels of IL-1RA in GCF and faster bone resorption in periodontitis and orthodontic tooth movement. 19,20 Our finding seems to support this association: The down-regulation of IL-1RA in the periodontal tissues during tooth eruption could allow for greater mineralized tissue resorption and may help explain the low IL-1RA concentration in the GCF of resorbing teeth.…”
Section: Discussionsupporting
confidence: 73%
“…5,17 The role of IL-1RA as an important inhibitor of bone remodeling is well documented in the literature, 3,18 and some studies show a positive correlation between decreased levels of IL-1RA in GCF and faster bone resorption in periodontitis and orthodontic tooth movement. 19,20 Our finding seems to support this association: The down-regulation of IL-1RA in the periodontal tissues during tooth eruption could allow for greater mineralized tissue resorption and may help explain the low IL-1RA concentration in the GCF of resorbing teeth.…”
Section: Discussionsupporting
confidence: 73%
“…29 Similarly, these findings were observed in our previous study. 7 In the literature, there are few studies investigating the relationship between AgP and IL-6 gene polymorphisms. 6,20,32,33 Supporting our results, Nibali et alreported that IL-6 GG genotype was associated with susceptibility to AgP.5 Similarly, ameta-analysis indicated that the IL-6(-174) G allele did not modify the risk of CP, but increased the risk of AgP.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Also, cytokine expressions a re a ffected by t he presence of f u nct ional gene polymorphisms. 6 Interleukin (IL)-6 is a pleiotropic cytokine released by many cell types, and its secretion levels are determined by the producing cell type and the genetic background of the source cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have investigated the relationship between clinical parameters and the levels of inflammatory cytokines such as IL-1β and IL-8 after SRP. Toker et al found that there were no significant correlations between the level of IL-1β and clinical parameters 6 weeks after initial periodontal therapy [33]. Research by Gamonal et al also showed a very weak correlation between clinical parameters and the levels of IL-1β and IL-8 2 months after SRP [34].…”
Section: Discussionmentioning
confidence: 94%